Spherical hard carbon material, preparation method thereof and application of spherical hard carbon material as battery negative electrode material
By using the oxidative cross-linking method of asphalt and starch in sodium ion batteries, a uniformly coated shell layer and cross-linking structure is formed, which solves the low yield and inhomogeneity problems in the preparation of spherical hard carbon materials, and improves the battery performance and Large-scale production of hard carbon.
Patent Information
- Application Number
- CN202411562310.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The preparation of spherical hard carbon materials in existing sodium ion batteries has problems such as low yield, uneven crosslinking and formation of skin core structures, which limits its large-scale application and electrical properties.
By dissolving asphalt on starch to form a uniformly coated shell layer, the crosslinking structure is formed at high temperature by oxidative crosslinking method to stabilize the spherical structure, and the starch active radicals are diffused through oxidative crosslinking to enhance the mechanical strength of the shell layer and carbon Yield.
It realizes efficient and uniform preparation of spherical hard carbon materials, improves sodium storage capacity and mechanical strength, avoids the formation of leather core structure, and promotes large-scale production of hard carbon and battery performance.
Smart Images

Figure CN119240662A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy sodium ion battery energy storage devices, and in particular to a spherical hard carbon material and a preparation method thereof and an application thereof as a battery negative electrode material. Background Art
[0002] With the rapid development of electric vehicles, portable electronic devices, and energy storage systems, the demand for high-performance, low-cost batteries is becoming increasingly urgent. However, although traditional lithium-ion batteries have superior performance, their large-scale application is limited by the scarcity and high cost of lithium resources. In contrast, sodium resources are abundant and low-cost, so the research and development of sodium-ion batteries has important strategic significance and economic value. In addition, sodium-ion batteries also show significant advantages in safety performance, low-temperature performance, and fast charging speed.
[0003] Hard carbon is considered to be an ideal negative electrode material for sodium ions due to its large interlayer and multi-pore structure. Among them, spherical hard carbon has a shorter and more uniform diffusion path for sodium ions in the negative electrode material due to its spherical structure; at the same time, the better fluidity and better stress distribution of spherical particles give it a higher compaction density, so spherical hard carbon has better rate performance and a higher surface loading of derived electrodes compared to other irregular hard carbon materials. Starch is a natural precursor for the preparation of spherical hard carbon due to its inherent spherical structure. However, it will produce a large amount of levoglucosan at high temperatures, which will directly volatilize or further convert into volatile tar, which will not only lead to a low carbon yield of only about 10%; at the same time, starch will partially decompose and produce water, become molten, and foam instantly under the action of volatile small molecules. In addition, the dense pores on the surface of the obtained spherical hard carbon also lead to a lower first coulomb efficiency of the derived negative electrode.
[0004] Asphalt has the advantages of high carbon content, developed aromatic structure, low price and abundant resources, and is an excellent precursor for preparing carbon materials. However, due to its soft carbon characteristics, liquid phase rearrangement occurs during the carbonization process, resulting in the formation of soft carbon with orderly carbon layers and small spacing. Air pre-oxidation cross-linking is considered to be one of the most economical and efficient ways to prepare asphalt-based hard carbon. Advanced Energy Materials, 2018, 8 (17): 1614-6840. A method of introducing a network cross-linked structure composed of oxygen-containing functional groups into asphalt through air heat treatment was reported to avoid liquid phase carbonization of asphalt. The derived hard carbon is softer than carbon, and the sodium storage capacity is increased from 94.0 mAh / g to 300.6 mAh / g. This method is simple and economical, but when the production line is scaled up, asphalt is prone to melt adhesion or uneven oxidation cross-linking in different regions, making it difficult to apply on a large scale. In addition, the cross-linking reaction is from the surface to the inside. Once the surface of the asphalt particles is oxidized to form a shell layer, the reaction will be difficult to penetrate and a skin-core structure will be easily formed. At the same time, this method directly changes the asphalt from thermoplastic to thermosetting through oxidative cross-linking, and the high adjustability of the asphalt is not fully utilized. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a spherical hard carbon material and a preparation method thereof and an application as a negative electrode material for a battery, aiming to achieve the preparation of a spherical hard carbon material with high sodium storage electrical performance and compaction through an economical and efficient method. The present invention dissolves asphalt on starch to form a uniform and dense coating shell layer, controls the thickness of the coating shell layer by adjusting the concentration of the asphalt solution, and utilizes oxidative cross-linking to not only form a cross-linked structure inside the asphalt, but also further strengthen the mechanical strength of the asphalt shell layer; at the same time, during the heat treatment process, the starch is oxidatively stable inside, so that the spherical structure is maintained. In addition, during oxidative cross-linking, the active free radicals and active small molecules generated by starch diffuse from the inside to the outside and are captured by the asphalt. While achieving asphalt cross-linking inside the shell layer, the overall yield is further improved, and uneven oxidation of asphalt to form a skin-core structure is avoided. The method provided by the present invention promotes the high added value utilization of asphalt, and further promotes the sustainable large-scale preparation of hard carbon economy, and promotes the development of the energy storage industry.
[0006] In order to achieve this goal, the present invention adopts the following technical solutions:
[0007] A spherical hard carbon material, the raw materials of which include asphalt, starch and solvent;
[0008] The mass ratio of the starch to asphalt is 1:1-10.
[0009] Preferably, the asphalt is a coated asphalt having a softening point of 200-300°C.
[0010] Preferably, the solvent comprises at least one of benzene, toluene, n-heptane, p-toluene and tetrahydrofuran;
[0011] Furthermore, the starch includes at least one of corn, potato, sweet potato and wheat starch.
[0012] Another object of the present invention is to protect a method for preparing the above-mentioned spherical hard carbon material, comprising the following steps:
[0013] (1) dissolving asphalt in a solution, then adding starch and stirring to react;
[0014] (2) drying the mixture of step (1) and then performing a depolymerization treatment to obtain a spherical precursor of asphalt-coated starch;
[0015] (3) introducing an oxidative atmosphere into the spherical precursor of the asphalt-coated starch in step (2) at high temperature, and performing a depolymerization treatment after crosslinking to obtain a spherical crosslinked precursor;
[0016] (4) The spherical cross-linked precursor of step (3) is carbonized under an inert atmosphere to obtain spherical hard carbon.
[0017] Preferably, the oxidizing atmosphere in step (3) comprises at least one of air, pure oxygen and ozone.
[0018] Preferably, the gas flow rate of the oxidizing atmosphere in step (3) is 50 to 300 ml / min.
[0019] Preferably, the cross-linking conditions in step (3) are: keeping at 200-250°C for 1-12 hours, with a heating rate of 1-5°C / min; and then keeping at 250-400°C for 1-12 hours, with a heating rate of 1-5°C / min.
[0020] Preferably, the inert protective atmosphere in step (4) is argon or nitrogen, the gas flow rate is 80-120 ml / min, and the heating rate is 1-5° C. / min.
[0021] Preferably, it is characterized in that the temperature in step (4) is 1000-1500° C. and the insulation time is 1-12 h.
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention uses low-cost asphalt and starch and a simple process to achieve controllable preparation of spherical hard carbon. Users can reasonably design and optimize the oxidative cross-linking process according to the electrical performance characteristics required by the usage scenario.
[0024] 2. The method provided by the present invention crosslinks the asphalt from the outside to the inside through oxidative crosslinking, and at the same time, the starch is pyrolyzed to generate active free radicals to crosslink the asphalt from the inside to the outside, thereby avoiding uneven oxidation of the asphalt to form a skin-core structure, and the shell layer formed by crosslinking has stronger mechanical strength than ordinary coating, which can limit the escape of light components to a certain extent and inhibit starch foaming. In addition, the synergistic effect of the two can effectively improve the carbon yield of the composite material.
[0025] 3. The preparation method of spherical hard carbon provided by the present invention has the characteristics of simple process and high efficiency. The prepared hard carbon has excellent uniformity and consistency, and is expected to realize the large-scale preparation of spherical hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM photo of the composite hard carbon of Example 1 of the present invention;
[0027] Figure 2 The XRD scanning patterns of the composite hard carbon of Examples 1, 2, 3, 4 and 5 of the present invention;
[0028] Figure 3 The charge and discharge curves of the composite hard carbon of Examples 1, 2, 3, 4, and 5 of the present invention are shown;
[0029] Figure 4 This is a rate performance diagram of the composite hard carbon of Example 1 of the present invention. Specific embodiments
[0030] Example 1
[0031] A method for preparing a spherical hard carbon material comprises the following steps:
[0032] (1) grinding and sieving asphalt with a softening point of 220° C. to obtain an asphalt raw material with a particle size of ≤20 μm;
[0033] (2) dissolving asphalt in tetrahydrofuran to prepare a 0.5 g / ml asphalt solution;
[0034] (3) adding potato starch at a mass ratio of 0.2 g / ml to the asphalt solution and stirring for 3 h. After standing for 6 h, transferring to a forced air drying oven and drying for 12 h, a spherical precursor was obtained after depolymerization treatment.
[0035] (4) The spherical precursor is transferred into a muffle furnace, heated from room temperature to 220°C in an oxygen atmosphere, oxidatively crosslinked for 6 hours, with an oxygen flow rate of 150 ml / min and a heating rate of 1°C / min, and then kept at 350°C for 3 hours at a rate of 5°C / min. After cooling, the precursor is depolymerized for 2 hours and sieved to obtain a spherical crosslinked precursor;
[0036] (5) The spherical cross-linked precursor is transferred to a tube furnace, heated to 1300° C. under an inert protective atmosphere of Ar, kept at this temperature for 4 h, and then naturally cooled to room temperature. The obtained hard carbon material is washed, filtered, and demagnetized to obtain a spherical hard carbon composite of starch and pitch. Figure 1 This is the SEM image of composite hard carbon.
[0037] The yield of the spherical hard carbon material prepared in Example 1 is 43.6%.
[0038] The spherical hard carbon material prepared in Example 1 is mixed with carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94:2:2:2 to form a slurry, and then the slurry is evenly scraped onto the current collector copper foil. After drying, the electrode pieces are cut. The battery is assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaPF6 (the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the current density of the hard carbon negative electrode is 20mA / g, the reversible specific capacity is 352.62mAh / g, and the first coulombic efficiency is 91.3%. The results are shown in Table 1 below. The rate performance is Figure 4 .
[0039] Example 2
[0040] A method for preparing a spherical hard carbon material comprises the following steps:
[0041] (1) grinding and sieving coated asphalt with a softening point of 250° C. to obtain an asphalt raw material with a particle size of ≤20 μm;
[0042] (2) dissolving asphalt in naphthalene to prepare an asphalt solution of 0.4 g / ml;
[0043] (3) adding potato starch at a mass ratio of 0.5 g / ml to the asphalt solution and stirring for 6 h. After standing for 4 h, transferring to a forced air drying oven and drying for 20 h, a spherical precursor was obtained after depolymerization treatment.
[0044] (4) The spherical precursor is transferred into a muffle furnace, heated from room temperature to 250°C in an air atmosphere, oxidatively crosslinked for 3 h, with an air flow rate of 150 ml / min and a heating rate of 2°C / min, and then kept at 300°C for 3 h at a rate of 2°C / min. After cooling, the precursor is depolymerized for 2 h and sieved to obtain a spherical crosslinked precursor;
[0045] (5) The spherical cross-linked precursor is transferred to a tubular furnace, heated to 1400°C under an inert protective atmosphere, kept warm for 3 hours and then naturally cooled to room temperature. The obtained hard carbon material is washed, filtered and demagnetized to obtain spherical hard carbon composited with starch and asphalt.
[0046] The yield of the spherical hard carbon material prepared in Example 2 is 45.2%.
[0047] The spherical hard carbon material prepared in Example 2 was mixed with carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94:2:2:2 to form a slurry, and then the slurry was evenly scraped onto the current collector copper foil. After drying, the pole pieces were cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaPF6 (the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 332.62mAh / g, and the first coulomb efficiency was 93.2%. The results are shown in Table 1 below.
[0048] Example 3
[0049] A method for preparing a spherical hard carbon material comprises the following steps:
[0050] (1) grinding and sieving coated asphalt with a softening point of 270° C. to obtain an asphalt raw material with a particle size of ≤20 μm;
[0051] (2) dissolving asphalt in toluene to prepare an asphalt solution of 0.6 g / ml;
[0052] (3) adding potato starch at a mass ratio of 1 g / ml to the asphalt solution and stirring for 6 h. After standing for 3 h, transferring to a forced air drying oven and drying for 15 h, a spherical precursor was obtained after depolymerization treatment.
[0053] (4) The spherical precursor is transferred into a muffle furnace, heated from room temperature to 230°C in an air atmosphere, oxidatively crosslinked for 4 h, with an air flow rate of 150 ml / min and a heating rate of 2°C / min, and then kept at 325°C for 3 h at a rate of 2°C / min. After cooling, the precursor is depolymerized for 2 h and sieved to obtain a spherical crosslinked precursor;
[0054] (5) The spherical cross-linked precursor is transferred to a tubular furnace, heated to 1200°C under an inert protective atmosphere, kept warm for 2 hours and then naturally cooled to room temperature. The obtained hard carbon material is washed, filtered and demagnetized to obtain spherical hard carbon composited with starch and asphalt.
[0055] The yield of the spherical hard carbon material prepared in Example 3 is 41.3%.
[0056] The spherical hard carbon material prepared in Example 3 was mixed with carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94:2:2:2 to form a slurry, and then the slurry was evenly scraped onto the current collector copper foil. After drying, the pole pieces were cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaPF6 (the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 327.46mAh / g, and the first coulomb efficiency was 91.28%. The results are shown in Table 1 below.
[0057] Example 4
[0058] A method for preparing a spherical hard carbon material comprises the following steps:
[0059] (1) grinding and sieving coated asphalt with a softening point of 280° C. to obtain an asphalt raw material with a particle size of ≤20 μm;
[0060] (2) dissolving asphalt in naphthalene to prepare a 0.5 g / ml asphalt solution;
[0061] (3) adding potato starch at a mass ratio of 0.8 g / ml to the asphalt solution and stirring for 4 h, leaving it to stand for 2 h and then transferring it to a forced air drying oven for drying for 8 h. After depolymerization treatment, a spherical precursor was obtained;
[0062] (4) The spherical precursor was transferred into a muffle furnace, heated from room temperature to 250°C in an air atmosphere, oxidatively crosslinked for 8 h, with an air flow rate of 150 ml / min and a heating rate of 3°C / min, and then kept at 375°C for 6 h at a rate of 5°C / min. After cooling, the precursor was depolymerized for 2 h and sieved to obtain a spherical crosslinked precursor;
[0063] (5) The spherical cross-linked precursor is transferred to a tubular furnace, heated to 1300°C under an inert protective atmosphere, kept warm for 2 hours and then naturally cooled to room temperature. The obtained hard carbon material is washed, filtered and demagnetized to obtain spherical hard carbon composited with starch and asphalt.
[0064] The yield of the spherical hard carbon material prepared in Example 4 is 39.8%.
[0065] The spherical hard carbon material is mixed with carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94:2:2:2 to form a slurry, and then the slurry is evenly scraped on the current collector copper foil. After drying, the electrode is cut. The battery is assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaPF6 (the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the current density of the hard carbon negative electrode is 20mA / g, the reversible specific capacity is 368.46mAh / g, and the first coulomb efficiency is 89.64%. The results are shown in Table 1 below.
[0066] Example 5
[0067] A method for preparing a spherical hard carbon material comprises the following steps:
[0068] (1) grinding and sieving coated asphalt with a softening point of 210° C. to obtain an asphalt raw material with a particle size of ≤20 μm;
[0069] (2) dissolving asphalt in naphthalene to prepare an asphalt solution of 0.6 g / ml;
[0070] (3) adding potato starch at a mass ratio of 0.3 g / ml to the asphalt solution and stirring for 10 h. After standing for 8 h, transferring to a forced air drying oven and drying for 24 h, a spherical precursor was obtained after depolymerization treatment.
[0071] (4) The spherical precursor is transferred into a muffle furnace, heated from room temperature to 220°C in an air atmosphere, oxidatively crosslinked for 4 h, with an air flow rate of 150 ml / min and a heating rate of 1°C / min, and then kept at 300°C for 6 h at a rate of 2°C / min. After cooling, the precursor is depolymerized for 2 h and sieved to obtain a spherical crosslinked precursor;
[0072] (5) The spherical cross-linked precursor is transferred to a tubular furnace, heated to 1400°C under an inert protective atmosphere, kept warm for 5 hours and then naturally cooled to room temperature. The obtained hard carbon material is washed, filtered and demagnetized to obtain spherical hard carbon composited with starch and asphalt.
[0073] The yield of the spherical hard carbon material prepared in Example 5 is 47.32%.
[0074] The spherical hard carbon material prepared in Example 5 was mixed with carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 94:2:2:2 to form a slurry, and then the slurry was evenly scraped onto the current collector copper foil. After drying, the pole pieces were cut. The battery was assembled in a glove box with Ar atmosphere, using metallic sodium as the counter electrode and 1M NaPF6 (the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1) solution as the electrolyte to assemble into a CR2032 button cell. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 334.66mAh / g, and the first coulomb efficiency was 94.34%. The results are shown in Table 1 below.
[0075] Table 1 Properties of spherical hard carbon prepared in Examples 1-5;
[0076] Example Yield (%) Reversible specific capacity (mAh / g) First coulombic efficiency (%) Example 1 43.6% 352.62 91.3% Example 2 45.2% 332.62 93.2% Example 3 41.3% 327.46 91.28% Example 4 39.8% 368.46 89.64% Example 5 47.32% 334.66 94.34%
Claims
1. A spherical hard carbon material, characterized in that: Raw materials include asphalt, starch, and solvents; The mass ratio of the starch to asphalt is 1:1-10.
2. The spherical hard carbon material according to claim 1, characterized in that The asphalt is a coated asphalt with a softening point of 200-300°C.
3. The spherical hard carbon material according to claim 1 or 2, characterized in that: The solvent includes at least one of benzene, toluene, n-heptane, p-toluene and tetrahydrofuran.
4. The spherical hard carbon material according to any one of claims 1 to 3, characterized in that: The starch includes at least one of corn, potato, sweet potato and wheat starch.
5. A method for preparing the spherical hard carbon material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving asphalt in a solution, then adding starch and stirring to react; (2) drying the mixture of step (1) and then performing a depolymerization treatment to obtain a spherical precursor of asphalt-coated starch; (3) introducing an oxidative atmosphere into the spherical precursor of the asphalt-coated starch in step (2) at high temperature, and performing a depolymerization treatment after crosslinking to obtain a spherical crosslinked precursor; (4) The spherical cross-linked precursor of step (3) is carbonized under an inert atmosphere to obtain spherical hard carbon.
6. The method according to claim 5, characterized in that The oxidizing atmosphere in step (3) includes at least one of air, pure oxygen and ozone.
7. The method according to claim 5, characterized in that The gas flow rate of the oxidizing atmosphere in step (3) is 50 to 300 ml / min.
8. The method according to claim 5, characterized in that The cross-linking conditions in step (3) are: keeping at 200-250°C for 1-12 hours, with a heating rate of 1-5°C / min; and then keeping at 250-400°C for 1-12 hours, with a heating rate of 1-5°C / min.
9. The method according to any one of claims 5 to 8, characterized in that: The inert protective atmosphere in step (4) is argon or nitrogen, the gas flow rate is 80-120 ml / min, and the heating rate is 1-5°C / min.
10. The method according to any one of claims 5 to 9, characterized in that: In step (4), the temperature in step (4) is 1000-1500° C., and the insulation time is 1-12 hours.
Citation Information
Patent Citations
Pyrolysis amorphous carbon material and preparation method and application thereof
CN105098186A
Preparation method of hollow carbon spheres
CN110482521A
Hard carbon / graphite composite negative electrode material and lithium ion battery as well as preparation method and application thereof
CN111244407A
Asphalt / starch-derived hard carbon, preparation method thereof and negative electrode material containing asphalt / starch-derived hard carbon
CN116621158A
Method for preparing silicon-carbon negative electrode material from biomass-based carbon aerogel
CN118771349A
